Conservation strategies for sacred village of Dhapewada Maharashtra/ - Zadgaonkar, Dhanashree (SPA Bhopal, 2022)
This thesis aims to propose conservation strategies to preserve the sense of continuityof the sacred village of Dhapewada, Maharashtra, by conserving its tangibleandintangible heritage. The village Dhapewada, Kalmeshwar, is a pilgrimdestinationhavinga strong organic human network as it results of a social order which has takenshapeasa religious nucleus for Hindus and is called as "Vidarbhache Pandharpur", havingShri Vitthal Rukmini temple on the banks of Chandrabhaga River and many small templesdedicated to Lord Krishna, Hanuman etc. and many wadas and mathas spreadacrossthe village. Pilgrim destinations act as nucleus that attract pilgrims fromall overlandscape. Some impact community at large and some are a regional variationorrepresentation of a larger phenomenon. These destinations must deal withaneverincreasing inflow of people focused on a specific location. This necessitates theregularexpansion and regulation of current facilities. The pilgrim locations havedifferent spiritual cycles, ranging from seasonal to yearly to periodical where large crowds converge. As a result, the management of this inflow varies depending on theseasonand other conditions. The surrounding infrastructure is under pressure of theof theseactivities in several ways. Historic buildings in this case are often ignoredor aremismanaged and hence action must be performed in accordance with thelivingconditions of the population. The expected outcomes would include spiritual importanceof Dhapewada as a tirtha and its association with Pandharpur by mapping of regional context through procession routes and its management round the year tokeepthesacredness alive.
Keywords: Conservation strategies for sacred village; Dhapewada Maharashtra